Application of porous building materials in low-rise housing construction - Dolmatov Sergey; Soboleva Anastasia; Voinash Sergey; Zagidullin Ramil; Yakushev Adel; Rzhavtsev Andrey; Sokolova Viktoriia (E3S Web of Conferences)
The enclosing structure made of porous building materials was considered as the object under study in the work. Let us consider four types of building wall materials (expanded clay concrete, porous ceramics, foam concrete and porous arbolite). Solid-state simulation modeling methods were used in the Elcut and Compass3D software packages. The calculation results showed that the heat flux at the wall made of expanded clay concrete is - 140.38 W/m2, from a porous ceramic block - 41.66 W/m2, from porous arbolite - 16.85 W/m2, foam concrete - 66.96 W/m2, the data were obtained at an external temperature of - 20°C and an internal temperature of +20°C. For an external temperature of -30°C, the heat flow at the wall made of expanded clay concrete is -175.47 W/m2, ceramic porous block - 52.1 W/m2, porous arbolite - 21.1 W/m2, foam concrete - 83.7 W/m2. The costs of heating the facility built from the materials considered were also determined. Solid fuel generation (coal and firewood) was adopted as a heat source. It turned out that the most expensive to heat a house made of expanded clay concrete, the cheapest was the maintenance of a facility made of porous arbolite.